A pathway for wisdom-focused education. Issue 1 (2nd January 2020) - Huynh, Alex C.; Grossmann, Igor
ABSTRACT: Interest in the topic of wisdom-focused education has so far not resulted in empirically validated programs for teaching wisdom. To start filling this void, we explore the emerging empirical evidence concerning the fundamental elements required for understanding how one can foster wisdom, with a particular focus on wise reasoning. We define wise reasoning through a combination of intellectual humility, recognition of world in flux/change, open-mindedness to diverse viewpoints, and search for compromise/integration of diverse perspectives. In this article, we review evidence concerning how wise reasoning can be facilitated through experiences, teaching materials, environments and cognitive strategies. We also focus on educators, reviewing emerging evidence on how the process of explaining and guiding others impacts one's wisdom. We conclude by discussing the development of wisdom-focused education, proposing that greater attention to the situational demands and the variability in wisdom-related characteristics across social contexts should play a critical role in its development.